Worldwide gene pool of fiber flax at VIR, and breeding of rust-resistant varieties - S. N. Kutuzova; E. A. Porokhovinova; N. B. Brutch; A. V. Pavlov (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. There are strict requirements for a modern flax cultivar. It must have a whole set of valuable characters, including rust resistance.Materials and methods. The flax collection of 2485 accessions held by VIR was evaluated using artificial provocative infection.Results. Almost all domestic and foreign accessions and varieties collected before 1957 were highly or extremely susceptible to rust. Five Russian kryazhs and cv. ‘GDS-3’ developed at VIR were found to retain rust resistance up to the present moment. Lines derived from them and from three foreign varieties, with an identified number of the original effective R genes, were submitted to breeders. Nineteen donors with a set of economically useful traits, analogous to cvs. ‘Orshansky 2’ and ‘Prizyv 81’ and carrying the same genes, were produced and distributed to breeders. The VIR collection holds 10 donors of rust resistance with high fiber content developed at the All-Russian Research Institute of Flax. Some donors of resistance to other diseases released by the same Institute also possess high rust resistance, thus forming a rich stock of source material. The first cultivar relatively resistant to rust (‘L-1120’) was released in 1951. Possessing polygenic resistance, it was also resistant to Fusarium wilt and lodging, so it was widely used for breeding other cultivars with similar characteristics. As their cultivation expanded, the harvest losses caused by rust dropped. The first rust-resistant cultivar with oligogenic resistance (‘Tomsky 16’) appeared in 1990. By now, many cultivars protected by R genes of rust resistance have been developed. They combine this trait with resistance to Fusarium and lodging, high yield, and high fiber content. Flax rust incidence is not a problem anymore.Conclusion. Plant breeders have at their disposal a rich stock of source material preserved in the VIR collection to produce resistant flax cultivars. The use of rust resistance donors in hybridization cannot disrupt the most important properties of a cultivar.